2012
DOI: 10.1128/iai.00521-12
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Advantage of Borrelia burgdorferi with Outer Surface Protein BBA03 during Tick-Mediated Infection of the Mammalian Host

Abstract: Linear plasmid lp54 is one of the most highly conserved and differentially expressed elements of the segmented genome of the Lyme disease spirochete Borrelia burgdorferi. We previously reported that deletion of a 4.1-kb region of lp54 (bba01 to bba07 [bba01-bba07]) led to a slight attenuation of tick-transmitted infection in mice following challenge with a large number of infected ticks. In the current study, we reduced the number of ticks in the challenge to more closely mimic the natural dose and found a pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 58 publications
2
34
1
Order By: Relevance
“…These data suggest that there was a greater probability of mice becoming infected with Bb ⌬A66 when more ticks fed to completion and may explain the results of the latter trials whereby mutant-infected mice usually had 4 or more ticks collected at the end of feeding. Bestor et al observed a similar phenomenon in experiments whereby an isolate lacking the genes bba01-07 was infectious by tick bite when 20 ticks per mouse were used, but not when the infestation was reduced to 3 ticks per mouse (37,38).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…These data suggest that there was a greater probability of mice becoming infected with Bb ⌬A66 when more ticks fed to completion and may explain the results of the latter trials whereby mutant-infected mice usually had 4 or more ticks collected at the end of feeding. Bestor et al observed a similar phenomenon in experiments whereby an isolate lacking the genes bba01-07 was infectious by tick bite when 20 ticks per mouse were used, but not when the infestation was reduced to 3 ticks per mouse (37,38).…”
Section: Discussionmentioning
confidence: 80%
“…Recent research investigating borrelia-vector interactions have focused on inactivation of global regulators, individual genes, and replicons to advance our understanding of B. burgdorferi tick colonization and persistence and vector transmission mechanisms (1,4,7,18,(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54). The loss of BBA66 activity did not completely abolish the ability of B. burgdorferi to invade the host by tick bite (at least when more than 4 ticks/mouse fed to repletion), but mouse infectivity was significantly impaired.…”
Section: Discussionmentioning
confidence: 99%
“…The findings reported here demonstrate that homologous B. burgdorferi is unable to effectively coinfect or superinfect an immunocompetent mouse host. The inability of in vitro-grown B31-A3 clones to establish culture-detectable coinfection may pose a limitation to competitive infection experiments used to assess colonization defects of isogenic B. burgdorferi clones after coinoculation (57). The results also show that host adaptation of spirochetes does not enable homologous B. burgdorferi clones to superinfect C3H mice.…”
Section: Discussionmentioning
confidence: 94%
“…The fourth protein in this set, BBA03, was also found solely in the IM in the present study. A prior well-controlled localization study remained equivocal in that BBA03 was found by immunofluorescence to be partially surface exposed but at the same time was protected from proteinase K in intact, but not permeabilized, cells (64). (ii) Two IM lipoproteins, BB0227 and BBB27, were localized to the inner leaflet of the OM in one of our earlier studies (57); we now believe that these localization results were erroneous due to contamination of the OMV fraction and a less-stringent interpretation of the data.…”
Section: Figmentioning
confidence: 92%